2020
DOI: 10.1002/ccd.28998
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term clinical outcomes from use of Sirolimus coated balloon in coronary intervention; data from real world population

Abstract: Background Use of drug coated balloons (DCBs) in coronary intervention is escalating. There is a plethora of data on Paclitaxcel‐DCB. However, when it comes of stents, Limus‐drugs are preferred over Paclitaxel. There is very limited data on Sirolimus coated balloons (SCB). MagicTouch‐SCB (Concept Medical, FL) elutes Sirolimus via nano‐technology and have been used in our centers since March 2018. We report a mid‐term follow‐up with this relatively novel‐technology. Methods and results We retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…2,3 However, their use has also been extended to de novo lesions, especially in patients and lesion subsets where stents are not ideal such as small vessels, diffuse disease, side-branches, and patients with high-bleeding risk (HBR) who may not be able to take dual antiplatelet therapy for an extended period. [4][5][6][7] The Use of DCBs in coronary intervention is escalating due to a consistent trickle of positive data. Current data supports the use of DCBs in small vessels as they are found to be non-inferior to stents and some studies even show superiority.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, their use has also been extended to de novo lesions, especially in patients and lesion subsets where stents are not ideal such as small vessels, diffuse disease, side-branches, and patients with high-bleeding risk (HBR) who may not be able to take dual antiplatelet therapy for an extended period. [4][5][6][7] The Use of DCBs in coronary intervention is escalating due to a consistent trickle of positive data. Current data supports the use of DCBs in small vessels as they are found to be non-inferior to stents and some studies even show superiority.…”
Section: Introductionmentioning
confidence: 99%
“…DCB treatment has received a class 1A recommendation for the treatment of both bare metal stent (BMS) and DES ISR in the 2018 ESC guidelines on myocardial revascularization 25 . Afterward, various studies have trials were performed to evaluate whether DCB are effective in de‐novo coronary lesions, specifically in small coronary vessels, or to assess the safety and efficacy of newer generation DCBs 7,26‐30 . Regarding small de novo lesions, the BASKET‐SMALL 2 trial and RESTORE‐SVD trial showed that DCB was noninferior to DES in regards of clinical outcomes 7,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the PICCOLETO II presented that the Elutax SV DCB was superior for late lumen loss compared with a DES 30 . Moreover, Basavarajaiah et al evaluated the efficacy and safety of a novel Sirolimus coated balloons, the MagicTouch‐SCB (Concept Medical, FL), showing low rates of hard endpoints and acceptable MACE rates 28 . This DCB applied a technique of encapsulating the poor lipophilic limus‐drug in a lipophilic nano‐carrier, so as to overcome the Achilles heel for Limus‐drugs to be used in balloon technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With its long and successful history in coronary drug-eluting stents (DES), sirolimus has attracted the attention of researchers investigating new DCB technologies. Sirolimus-coated balloons have so far shown promising results in inhibition of restenosis after percutaneous coronary interventions (PCIs) in a small number of patients included in clinical studies [4][5][6][7][8]. Furthermore, a wide range of other drugs with potential antiproliferative, anti-inflammatory, or antithrombotic actions might be candidates for balloon coating.…”
Section: Introductionmentioning
confidence: 99%